Blood prefabricated hydroxyapatite/tricalcium phosphate induces ectopic vascularized bone formation via modulating the osteoimmune environment. (22nd June 2018) - Wei, Fei; Liu, Guanqi; Guo, Yuanlong; Crawford, Ross; Chen, Zetao; Xiao, Yin
Abstract : Blood prefabricated hydroxyapatite/tricalcium phosphate induces ectopic vascularized bone formation via modulating the osteoimmune environment. Abstract : Successful bone healing depends significantly on the structure of blood clots and the functional responses of blood cells. Despite the importance of blood clots in osteogenesis, few studies have investigated the effects of blood clots during material-mediated bone regeneration. In this study, we implanted the bone graft substitute hydroxyapatite/tricalcium phosphate (HA/TCP) subcutaneously, with or without blood prefabrication, to evaluate the effects of blood clots on material-mediated bone formation. We observed that blood prefabricated HA/TCP induced ectopic vascularized bone-like structures, implying that blood prefabrication can induce a microenvironment sufficient for HA/TCP-mediated bone formation. The possible mechanisms were related to (1) modification of the fibrin network, which facilitates MSCs recruitment and differentiation, (2) modulation of the early osteoimmune environment with the upregulation of osteogenic factor BMP2, and (3) improved expression of VEGF and the enhancement of angiogenesis. These results demonstrate the multifaceted effects of blood clots in regulating osteogenesis, osteoclastogenesis, immune responses, and angiogenesis. Therefore, blood prefabrication can serve as a valuable strategy to improve the osteogenic capacity of materials, and prefabricating materials with blood clots prior to implantation should be encouraged. New generation bone substitute materials could target the modulation of a favorable blood clot response for improved bone regeneration.